Self-assessment by computer-assisted interpreter training (CAIT) for practising interpreters : Parliament as a case in study - Deysel, Elizabeth (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)-- Stellenbosch University, 2018.